Preparing Indonesian Students for the Post-Truth Era: The Educational Potential of the Scientific, Social and Contextual (SSC) Framework for AI Literacy and Achieving SDGs - Laila Margaretha Nur Habibah (International Forum of Researchers and Lecturers, 2026)
The increasing volume of misinformation, disinformation, and AI-generated content has reshaped how information is produced, shared, and consumed, creating new challenges for education in the post-truth era. Students are expected not only to access information but also to evaluate its credibility, interpret evidence, and make responsible decisions in increasingly complex digital environments. Despite this need, literacy instruction in Indonesia has largely focused on reading comprehension, with limited attention to integrating scientific reasoning, social responsibility, and contextual understanding. This paper explores the potential of the Scientific, Social, and Contextual (SSC) Framework as a conceptual approach to preparing Indonesian students for these emerging challenges while contributing to the achievement of the Sustainable Development Goals (SDGs). Adopting a conceptual literature review, the study draws on recent scholarship concerning post-truth, critical literacy, scientific literacy, digital citizenship, AI literacy, contextual learning, and education for sustainable development. The review suggests that the SSC Framework offers a holistic perspective by combining evidence-based reasoning, ethical and collaborative engagement, and contextual problem-solving. These interconnected dimensions can strengthen students' critical literacy, digital resilience, and capacity to respond thoughtfully to misleading information and AI-generated content. The paper contributes a conceptual foundation for integrating the SSC Framework into curriculum design, teaching practices, and future educational research. By promoting critical, responsible, and sustainable learning, the framework supports the development of competencies aligned with SDG 4 (Quality Education), SDG 16 (Peace, Justice and Strong Institutions), and SDG 17 (Partnerships for the Goals).